Growth and yield difference due to application of various levels of gibberelic acid in local and BARI falon-1 (Progressive Agriculture, 2016)
An experiment was carried out at the research farm of Patuakhali Science and Technology University (PSTU) during the period from November 2010 to April 2011 to study on growth and yield performance of cowpea (BARI Falon-1 and local Falon) with different concentration of GA3 (control, 25.00, 33.33, 50.00 and 100.00 ppm) to find out the suitable variety and optimum level of  gibberelic acid (GA3) application which would be also suitable to cultivate under coastal region of Patuakhali. Among the treatments, GA3 at 33.33 ppm treated plant of BARI Falon1 showed the better performance on growth and yield contributing characters. As a result, the tallest plant (62.53 cm), number of leaves and branches plant1 (28.67 and 20.07, respectively), TDM (83.99 g), CGR (1.68 cm2 day-1), RGR (0.729 cm2 day-1) and NAR (1.275 cm2 day-1) were exhibited from the variety BARI Falon-1 with the spraying of GA3 at 33.33 ppm at harvest. Yield contributing characters had also higher such as pods plant1 (11.67), length of pod (17.20 cm), seeds pod1 (16.80), 100-seed weight (12.49 g), seed yield (20.16 g plant-1 and 3139.93 kg ha-1) and harvest index (24.04%) with the variety BARI Falon1 whily it was treated by 33.33 ppm GA3. Hence, it can be concluded that the application of GA3 up to 33.33 ppm than other GA3 levels and BARI Falon-1 than Local Falon would be the most suitable for obtaining the greater yield of cowpea under the coastal area of Patuakhali region. So, considering the above observation, BARI Falon-1 therefore is suggested to cultivate in Patuakhali region while 33.33 ppm GA3 would be also optimum level for the better prodcution of cowpea.Progressive Agriculture 27 (2): 94-100, 2016